ANALISIS IMPLEMENTASI PROGRAM GERAKAN LITERASI SEKOLAH PADA PESERTA DIDIK KELAS V DI UPTD SD ISLAM NEGERI COKROAMINOTO 2 KALABAHI - Nurfitri Arsyifah Burhan (CV. ADIBA ASIHA AMIRA, 2026)
The aim of this study was to determine the role of teachers in implementing the school literacy movement programme at the Cokroaminoto 2 State Islamic Primary School (UPTD) in Kalabahi. This was a qualitative study using a descriptive method. The data sources for this study were the headteacher and class teachers. Data collection techniques included observation, interviews and documentation. The findings of this study indicate that the School Literacy Movement at the UPTD Cokroaminoto 2 State Islamic Primary School in Kalabahi has been implemented in every class since 2023; for example, pupils read books for 15 minutes before lessons begin, in accordance with the school literacy movement guidelines issued by the Ministry of Education and Culture, which comprise three stages: familiarisation, development and learning. Furthermore, pupils are able to carry out these literacy activities effectively in accordance with the school’s policies as communicated by the headteacher and class teachers.